Penerapan Super Enkripsi Algoritma Autokey Cipher dan El-Gamal File Gambar - Rio Andika; Rizky Fajar Sitepu; Putri Ramadhani; Rizka Nova Fitria; Achmad Fauzi (Jurnal Sistem Informasi Kaputama (JSIK), 2025)
Autokey Cipher is a classic encryption technique that uses substitution methods, providing a higher level of security compared to other classical techniques such as Caesar and Vigenère ciphers. It generates keys that match the length of the plaintext, ensuring that each character of the original data has a corresponding key character, which is crucial for effective encryption.on the other hand, the ElGamal algorithm is an asymmetric encryption method that uses different keys for encryption and decryption, relying on prime numbers and discrete logarithms to secure messages. This algorithm was chosen because of its strong security features, making it difficult for unauthorized users to decrypt information without the right key. The combination of these two algorithms aims to create a more secure encryption system. Autokey Cipher contributes complex substitution techniques, while ElGamal adds an additional layer of security through an asymmetrical key structure. This dual approach is very beneficial for protecting sensitive data, such as image files, from unauthorized access. highlighting the potential of these combined methods to provide stronger defenses against a wide range of security threats in the digital landscape